Semiotic Analysis of Colonial and Postcolonial Elements in Coca-Cola Advertisements - (:unkn) unknown (MARMARA UNIV, FAC COMMUNICATION, 2020)
Advertising is not just a tool for promoting or purchasing a product or service. More than this function, advertising is an important mass communication tool that can change and organize life, capable of creating meanings and producing discourses. The concept of colonialism, which historically transformed the world we live in, is a motive that can observed in advertisements. This study examines two Coca-Cola commercials by focusing on the colonial and postcolonial elements in the advertisements through a semiotic analysis. The analysis of the advertisements points out that there are parallels between the language applied by the colonizer over the colonized in historical period and the discourses in Coca-Cola advertisements. In both advertisements, there is a specific language and meaning transmission about non-European others, leading to signs produced by the Western self. In addition to the images created by the West regarding the indigenous other, advertisements also convey the qualities that the West has built for its identity in the historical process. The advertisements reflect the relationships between the exploiter and the exploited, eventually leading to discourses constructed from a Western perspective. In highlighting the domination of the West over the colonized, Roland Barthes' semiotic analysis was applied to advertisements, to explore colonial and postcolonial ideologies at the connotative and mythic levels.
Keywords: Advertising; Semiotics; Colonialism; Postcolonialism; Coca-Cola